Nicotine Metabolism-Related Genetic Polymorphisms Associated with Smoking Cessation in Korean Men: A Candidate Gene Association Study in a Korean Cohort - Jae-Min Park; Ja-Eun Choi; Ji-Won Lee; Kyung-Won Hong (Lifestyle Genomics)
Introduction: Smoking cessation is influenced by genetic and environmental factors, particularly genetic polymorphisms influencing nicotine metabolism. This study investigated the association between specific nicotine metabolism-related genetic variants and smoking cessation among Korean men. Methods: A candidate gene association study was performed targeting single nucleotide polymorphisms (SNPs) within nicotine metabolism-related genes. Participants were categorized as never, former, or current smokers. A Genetic Risk Score (GRS) was computed using significant SNPs to evaluate cumulative genetic influence. Results: Six SNPs showed significant association with smoking cessation in a Korean cohort. A higher GRS was associated with increased odds of current smoking compared to former smoking (OR = 1.18, 95% CI: 1.12–1.25, p < 0.001). Conclusion: This study indicates a substantial genetic component in smoking cessation, highlighting the importance of population-specific approaches, and may aid personalized smoking cessation strategies based on genetic predisposition among Koreans.